Implementasi Perlindungan Anak terhadap Eksploitasi Pengamen Badut di Gorontalo - Samuel Samuel; Lisnawaty W Badu; Nuvazria Achir (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the implementation of Article 88 of Law Number 35 of 2014 concerning Child Protection against child exploitation as clown buskers in Gorontalo City, as well as identify the factors that cause the exploitation. This study uses an empirical legal method with a descriptive approach to obtain data related to behavior, social conditions, and symptoms in society. Data was collected through observation, interviews, and documentation. The results of the study show that the implementation of Law Number 35 of 2014 has not been optimal, because the relevant apparatus, such as the Social Service and Satpol PP, have not followed up on this case with a criminal law approach, but only with coaching and administrative efforts. This causes child exploitation to continue without strict legal sanctions. The factors that cause the exploitation of children as buskers in clown costumes in Gorontalo City include economic, family, environmental factors, lack of law enforcement, and low legal awareness in interrelated communities. This research emphasizes the importance of synergy between the government, law enforcement officials, social institutions, and the community to reduce child exploitation practices through preventive, repressive, and rehabilitative efforts in a sustainable manner.